Mitochondrial dysfunction in hypertension: mechanistic pathways and therapeutic implications - Jiao Tian; Lin Yi; Yuyuan Lu; Yushun Kou; Lingna Zhang; Penghui Jin; Xiaoke Wang; Tao Wu; Xin Yang; Yiyuan Wang; Ruiling Ma (Functional & Integrative Genomics, 2026)

Unraveling the spatial chemical heterogeneity of Lentinula edodes: Integrative metabolomics and machine learning for cultivar and origin classification - Shenglong Lu; Chaoyi Shen; Ben Niu; Ruiling Liu; Huizhi Chen; Hangjun Chen; Xiangjun Fang; Lishu Wang; Ming Yin; Weijie Wu; Haiyan Gao (Food Chemistry, 2026)

DlNAC41 and DlNAC100 transcription factors modulate longan pulp breakdown via adjusting the expression of cell wall degradation-related genes - Hui Wang; Wenlong Zhou; Xinyue Mu; Zhongqi Fan; Ruiling Zhuo; Yihui Chen; Wangjin Lu; Boqiang Li; Shiping Tian; Yifen Lin; Hetong Lin (Postharvest Biology and Technology, 2026)

DlbHLH66 transcription factor is involved in the acidity differences in the pulp of fresh longan cv. ‘Fuyan’ and ‘Dongbi’ during storage - Zhongqi Fan; Lingzhen Zeng; Shucheng Li; Hui Wang; Ruiling Zhuo; Yifen Lin; Yihui Chen; Wangjin Lu; Boqiang Li; Shiping Tian; Hetong Lin (Postharvest Biology and Technology, 2026)

Strain-engineered selenium vacancies in MoSe2 cocatalysts to redirect photocarrier trapping for efficient hydrogen evolution - Siyi Zhang; Ni Hu; Zhenfei Fu; Shilong Suo; Qing Han; Ziwu Han; Ziyue Zhang; Ruiling Zhang; Bing Jin; Zhenhua Zhang; Zhihong Lu; Pengfei Fang (Chemical Engineering Journal, 2025)

The anti-Alzheimer's disease effects of ganoderic acid A by inhibiting ferroptosis-lipid peroxidation via activation of the NRF2/SLC7A11/GPX4 signaling pathway - Qingyang Lu; Nan Shao; Ziyi Fang; Zhaorong Ouyang; Yiran Shen; Ruiling Yang; Houli Liu; Biao Cai; Tao Wei (Chemico-Biological Interactions, 2025)

Spatiotemporal variability of leaf critical senescence age across northern lands and its key drivers - Xingli Xia; Cuihai You; Ruiling Lu; Ning Wei; Chenyu Bian; Ying Du; Erqian Cui; Songbo Tang; Zhiqin Tu; Jiaye Ping; Kun Huang; Jianyang Xia (Global and Planetary Change, 2024)

Identification of extracted antioxidants from Citrus aurantium 'Changshanhuyou' residue against digestive enzyme activities and airway smooth muscle cells proliferation using UPLC-MS/MS - Xinyue Zhou; Junyang Wang; Han Wang; Peng Lu; Qiong Huang; Ming Huang; Ruiling Lv; Donghong Liu; Wenjun Wang (Food Bioscience, 2024)

Drought shortens subtropical understory growing season by advancing leaf senescence - Huanfa Sun; Liming Yan; Zhao Li; Wanying Cheng; Ruiling Lu; Xingli Xia; Jiaye Ping; Chenyu Bian; Ning Wei; Cuihai You; Songbo Tang; Ying Du; et al. (Global Change Biology, 2024)
Subtropical forests, recognized for their intricate vertical canopy stratification, exhibit high resistance to extreme drought. However, the response of leaf phenology to drought in the species‐rich understory remains poorly understood. In this study, we constructed a digital camera system, amassing over 360,000 images through a 70% throughfall exclusion experiment, to explore the drought response of understory leaf phenology. The results revealed a significant advancement in understory leaf senescence phenology under drought, with 11.75 and 15.76 days for the start and end of the leaf‐falling event, respectively. Pre‐season temperature primarily regulated leaf development phenology, whereas soil water dominated the variability in leaf senescence phenology. Under drought conditions, temperature sensitivities for the end of leaf emergence decreased from −13.72 to −11.06 days °C −1 , with insignificance observed for the start of leaf emergence. Consequently, drought treatment shortened both the length of the growing season (15.69 days) and the peak growth season (9.80 days) for understory plants. Moreover, this study identified diverse responses among intraspecies and interspecies to drought, particularly during the leaf development phase. These findings underscore the pivotal role of water availability in shaping understory phenology patterns, especially in subtropical forests.

Nanoparticle encapsulation using self-assembly abietic acid to improve oral bioavailability of curcumin - Ying Han; Hua Zhang; Haitian Zhao; Shiyao Fu; Ruiling Li; Zhili Wang; Yangxin Wang; Weihong Lu; Xin Yang (Food Chemistry, 2024)

Extensive regulation of pH-responsive transcription factor PacC on secondary metabolism contributes to development and virulence of Botrytis cinerea - Ruiling Zhuo; Guangjin Li; Huaimin Peng; Yuanyuan Zong; Xiao Wang; Shasha Lu; Yong Chen; Zhanquan Zhang; Shiping Tian; Boqiang Li (Postharvest Biology and Technology, 2023)

Regulating cobalt chemical state by CeO2 facets preferred exposure for improved ethanol steam reforming - Ruiling Li; Chengyuan Liu; Li Li; Junjie Xu; Jinjin Ma; Jiaqi Ni; Jing Yan; Jun Han; Yang Pan; Yi Liu; Lilin Lu (Fuel, 2023)

Soil phosphorus drives plant trait variations in a mature subtropical forest - Erqian Cui; Ruiling Lu; Xiaoni Xu; Huanfa Sun; Yang Qiao; Jiaye Ping; Shuying Qiu; Yihua Lin; Jiehuan Bao; Yutong Yong; Zemei Zheng; Enrong Yan; et al. (Global Change Biology, 2022)
Earth system models are implementing soil phosphorus dynamic and plant functional traits to predict functional changes in global forests. However, the linkage between soil phosphorus and plant traits lacks empirical evidence, especially in mature forests. Here, we examined the soil phosphorus constraint on plant functional traits in a mature subtropical forest based on observations of 9943 individuals from 90 species in a 5‐ha forest dynamic plot and 405 individuals from 15 species in an adjacent 10‐year nutrient‐addition experiment. We first confirmed a pervasive phosphorus limitation on subtropical tree growth based on leaf N:P ratios. Then, we found that soil phosphorus dominated multidimensional trait variations in the 5‐ha forest dynamic plot. Soil phosphorus content explained 44% and 53% of the variance in the traits defining the main functional space across species and communities, respectively. Lastly, we found much stronger phosphorus effects on most plant functional traits than nitrogen at both species and community levels in the 10‐year nutrient‐addition experiment. This study provides evidence for the consistent pattern of soil phosphorus constraint on plant trait variations between the species and community levels in a mature evergreen broadleaf forest in the East Asian monsoon region. These findings shed light on the predominant role of soil phosphorus on plant functional trait variations in mature subtropical forests, providing new insights for models to incorporate soil phosphorus constraint in predicting future vegetation dynamics.

Spatial-temporal Evolution Characteristics and Decoupling Analysis of Influencing Factors of China’s Aviation Carbon Emissions - Ruiling Han; Lingling Li; Xiaoyan Zhang; Zi Lu; Shaohua Zhu (Chinese Geographical Science, 2022)

Region-dependent regulation of acute ethanol on γ oscillation in the rat hippocampal slices - Zhihua Liu; Feng Ren; Bin Yang; Hongxing Zhang; Fangli Guo; Xiangyang Zhang; Chengbiao Lu; Ruiling Zhang (Psychopharmacology, 2020)

Plant NE : a global database of plant biomass from nitrogen‐addition experiments - Xiaoni Xu; Ruiling Lu; Liming Yan; Jianyang Xia (Ecology, 2019)
The growth of terrestrial plants and the production of terrestrial ecosystems are highly dependent on the availability of nitrogen (N). During the past decades, the rate of global atmospheric N deposition has shown an increasing trend, greatly relieving N limitation on terrestrial plant growth. Thus, whether and how plant biomass will respond to increasing N deposition in the future is particularly important with regard to the function of terrestrial ecosystems. The N‐addition experiment is a major approach to study the ecological responses of plant species occurring in natural terrestrial ecosystems under N enrichment. In recent decades, many N‐addition experiments have been conducted across various plant functional types and terrestrial ecosystems, but their data on plant biomass have yet to be synthesized into a single database. Here, we present an open‐access database of measured plant biomass in N‐addition experiments (Plant NE ) collected from available publications in Web of Science. The reported mean, standard deviation, and sample size of plant biomass in both control and treatment plots were collected in each publication. As a result, the Plant NE database records 519 plant species from 4,599 observations in 348 published studies. It covers a wide geographical range (54.75° S–69.66° N; 157.80° W–175.30°E) and a broad natural climate zone (−10°C to 27.6°C; 94–7,000 mm) over the past three decades (1982–2018). Information related to the experimental site (i.e., latitude, longitude, country, ecosystem, experimental condition, temperature, and precipitation), biotic factors (i.e., species, plant category, plant age, planting pattern, and plant part), and N treatment (i.e., N dose, treatment interval and duration, and N addition with other treatments) is included in this database. We expect that the Plant NE database can contribute to the understanding of ecosystem productivity and biodiversity under increasing atmospheric N deposition and provide empirical data for model studies. There are no copyright restrictions; personal or noncommercial use of this database by researchers and teachers is encouraged. Researchers are requested to cite this paper if using all or part of the database. As we intend to keep this database up to date on GitHub (see Metadata S1 for details) and Zenodo ( https://doi.org/10.5281/zenodo.3359810 ), researchers are encouraged to inform us of the applications of this database.

Differential Immune Responses and Protective Effects in Avirulent Mycobacterial Strains Vaccinated BALB/c Mice - Laicheng Liu; Ruiling Fu; Xuefeng Yuan; Chunwei Shi; Shuling Wang; Xianyu Lu; Zhao Ma; Xiaoming Zhang; Weiyan Qin; Xionglin Fan (Current Microbiology, 2015)

Development and evaluation of a new interferon-gamma release assay for the diagnosis of tuberculosis infection in HIV-infected individuals in China - Liang Yu; Pingzheng Mo; Zeping Wei; Ruiling Fu; Mai Yang; Binying Ji; Jian Wang; Shu Li; Amie J. Strong; Neal Touzjian; Nicholas Kushner; Xi-En Gui; et al. (Infectious Diseases, 2015)